The Effectiveness of Village Fund Management to Improve The Welfare of The Padang Village Community, Trucuk District - Anggraini, Pristia; Mangindalat, Rosda Latipa (Universitas Bojonegoro, 2026)
The purpose of this study is to determine the effectiveness of Village Fund management in improving the welfare of the people of Padang Village, Trucuk District, using Okberi theory which emphasizes three main indicators: input, process, and output. The focus of the study is directed at measuring the extent to which Village Fund management can meet the needs of development and community empowerment, especially in the context of reducing poverty rates which have actually experienced an increasing trend over the past three years despite the continued increase in fund allocations. The main problems lie in the imbalance in priorities between physical development and community economic empowerment, limited citizen participation, and the suboptimal utilization of resources. Most previous researchers discuss the implementation or accountability of Village Funds in general in other areas, while this study measures effectiveness with Okberi theory specifically in Padang Village. Using qualitative methods through interviews, observations, and documentation, this study is expected to provide contextual empirical contributions, while producing more targeted policy recommendations to improve the effectiveness of Village Fund management, create a balance between physical development and community empowerment, and support the achievement of equitable and sustainable welfare.